Teacher Questioning Practices and Multidimensional Student Engagement in an Indonesian Primary EFL Classroom - Nina Rosiana Putri; Lusi Nurhayati; Ari Purnawan; Anita Triastuti (VELES Voices of English Language Education Society, 2025)
Teachers’ questioning plays a pivotal role in shaping classroom interaction and student engagement in English as a Foreign Language (EFL) settings, particularly in primary classrooms where learners have limited English exposure and content knowledge. In many Indonesian EFL classrooms, including those in Lampung, instructional interaction remains largely teacher-dominated, restricting students’ opportunities to participate actively in meaning-making. Responding to this issue, this qualitative case study investigates the types of questioning strategies employed by a primary EFL teacher, how these strategies are enacted in classroom interaction to stimulate student engagement, and the challenges encountered in implementing them with young learners. The participants consisted of one English teacher and eighteen third-grade students at a primary school in Lampung, selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and document analysis. The findings reveal four dominant types of teacher questions—factual, probing, divergent, and higher-order—each serving distinct interactional functions. Factual questions were predominantly used to check understanding and manage lesson flow, while probing questions supported elaboration and reasoning. Divergent questions encouraged idea generation and personal connections, and higher-order questions promoted critical thinking, evaluation, and dialogic interaction. These questioning practices were found to stimulate students’ behavioral, cognitive, and emotional engagement to varying degrees. Interview data further indicate that the teacher intentionally used questioning to monitor comprehension, activate prior knowledge, scaffold participation, and foster student engagement. However, challenges emerged related to students’ limited content knowledge and the teacher’s difficulty in responding to students’ divergent questions.